Rice resistance to stem borer. III. Effect of varieties on nutrition and development of the insect - Martins, José Francisco da Silva; Parra, José Roberto Postali; Mihsfeldt, Laila Herta (Pesquisa Agropecuaria Brasileira, 2014)
The relativa influence of the chemical composition of rice varieties IAC-25, IAC-47 and DD-48 on the nutrition and development of the rice stem borer (Diatraea saccharalis) was studied through larval feeding in artificial diets containing aqueous stem extracts. The nutritional index efficiency of conversion of digested food (ECD) was used. The diets based on the susceptible varieties IAC-25 and IAC-47 had a better nutritional quality than the diet of the resistant variety DD-48. The last diet consumption caused antibiosis symptoms in the insect. It was ascertained that antibiosis type of resistance in rice to D. saccharalis, duo to the biochemical factors of the plants, can reduce the survival and the growth rate of th larvae, induce adults deformation and affect the insect reproductive potential.